2015
DOI: 10.1111/1440-1681.12506
|View full text |Cite
|
Sign up to set email alerts
|

Nefopam analgesia and its role in multimodal analgesia: A review of preclinical and clinical studies

Abstract: SUMMARYNefopam is a non-opioid, non-steroidal, centrally acting analgesic drug used to prevent postoperative pain, primarily in the context of multimodal analgesia. This paper reviews preclinical and clinical studies in which nefopam has been combined with opioids, non-steroidal anti-inflammatory compounds, and paracetamol. This report focuses on the literature during the last decade and discusses the translational efforts between animal and clinical studies in the context of multimodal or balanced analgesia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 62 publications
1
59
1
3
Order By: Relevance
“…The analgesic efficacy of nefopam during the acute postoperative period was known from several preclinical and clinical studies. 5 7 Our results were also similar to previous studies examining acute postoperative pain, which showed that patients treated with nefopam reported severe pain less often. All patients received ketorolac routinely at the end of the surgery and meloxicam in the acute postoperative period.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The analgesic efficacy of nefopam during the acute postoperative period was known from several preclinical and clinical studies. 5 7 Our results were also similar to previous studies examining acute postoperative pain, which showed that patients treated with nefopam reported severe pain less often. All patients received ketorolac routinely at the end of the surgery and meloxicam in the acute postoperative period.…”
Section: Discussionsupporting
confidence: 90%
“…Nefopam has been studied in several animal models and various clinical settings, where it was found to be an effective analgesic adjuvant. 5 Perioperative use of nefopam reduced the postoperative consumption of morphine, with surgical pain relief after abdominal and orthopedic surgeries, 6 , 7 and it enhanced the analgesic effect of NSAIDs. 8 However, to our knowledge, no reported clinical study has evaluated the analgesic efficacy of nefopam in breast cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It inhibit the central synaptosomal reuptake of serotonin (5-hydroxytryptamine, 5-HT), norepinephrine and dopamine, it interacts directly with á2 -adrenoreceptors and modulate the calcium and sodium channels of the glutamatergic pathway and therefore decreasing the activation of postsynaptic glutamatergic receptors, like N-methyl-D-aspartate (NMDA), which has a specific role in hyperalgesia appearance [9]. In the first place, it was used as an antidepressant and as an antispasmodic drug due to its myorelaxant properties [10] but studies have shown its effectiveness in preventing acute postsurgical hyperalgesia [11] and modulation of non-surgical neuropathic pain [12]. It is a benzoxazocine known as 5-methyl-1-phenyl-1,3,4,6tetrahydro-2,5-benzoxazocine (C 17 H 19 NO) obtained from a non-sedative benzoxazocine and is a cyclized analogue of an antihistamine (diphenhydramine -C 17 H 21 NO) [13].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…The demonstration of the neuroprotective effect of acetaminophen finds echoes in the cardiology literature, where it is reported for antioxidant and anti-inflammatory properties [11]. In the brain, acetaminophen's mechanism of action may involve the inhibition of central cyclo-oxygenase COX-2 and COX-3 enzymes and the modulation of serotonergic system [12,13]. As well, acetaminophen enabled the lowering of oxidative stress-induced brain neuron damage through the inhibition of superoxide anion production, and an increased synthesis of anti-apoptotic protein Bcl-2 [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that nefopam did not interfere with the binding of MK801 to NMDA receptors in the glutamate pathway [18]. Indeed, it has been demonstrated that nefopam act on the glutamatergic pathway via modulations of calcium and sodium channels, that leads to decreased activation of postsynaptic glutamatergic receptors such as NMDA receptors [13]. To end, our observation suggests that an acute administration of nefopam at a dose of 20 mg/kg may induce postoperative analgesia without masking the pharmacological effect of a neuroprotective agent such as MK801.…”
Section: Discussionmentioning
confidence: 99%